Alive at work : the neuroscience of helping your people love what they do - Cable, Daniel M. (Harvard Business Review Press, 2018)
We've all seen the oft-cited Gallup poll that reports that an alarming majority of the workforce is disengaged and unmotivated. In Alive at Work, social psychologist Dan Cable argues that the reason for all the unhappiness is biological: organizations, in an effort to routinize work and establish clear-cut performance metrics, are suppressing what neuroscientists call our Seeking Systems, the part of our brain that craves exploration and learning. The good news is that organizations can activate our Seeking Systems, and, as Cable explains, it doesn't take extensive overhauls to their cultures to do so. With small changes, managers and supervisors can make meaningful impacts on our lives and restore our zest for work. For instance, the book reveals: how new hires exhibited their best traits and were less likely to quit in the future after sharing stories about themselves during on-boarding seminars, how Italian factory workers reduced their anxiety about a new process by playing with Legos, how employees at Make-A-Wish reduced burnout by crafting their own job titles. Filled with real-life examples from the author's own research and consulting, Alive at Work equips managers--and anyone looking to find more joy in their nine-to-five existence--with the guidance to maximize the curiosity and passion that lives within themselves and others.--